Assessing the scientific value and vulnerability of paleontological sites: a new analytic operational procedure - Faggi, Andrea; Bartolini-Lucenti, Saverio; Rook, Lorenzo (Frontiers in Earth Science, 2023)
Introduction: Paleontological heritage rarely receives the same legislative attention as archeological heritage. Part of the problem seems to be, at least in some contexts (e.g., Italy), the difficulty of acknowledging fossils as distinct assets from other cultural heritage objects and the lack of expertise among the administrative functionaries. This study aims to describe and test an objective analytic operational procedure that could allow for the assessment of the relevance of any fossiliferous site and its potential vulnerability in its present state. Methods: The estimations were obtained using several quantitative and qualitative parameters that could describe the probability of fossil recovery for each site (Pr) and the scientific and cultural interest of the locality (In). Each parameter has subcategories for better defining. The product of probability and interest results in the scientific value (S), generally expressed as a percentage (S*). The vulnerability index (V) of productive and active sites considers the use of the land (U) and the natural erosion (E). The parameters were thought to apply to any type of fossil locality. We tested the indexes on 22 localities (7 of which were with paleoichnological records and 15 with direct body-fossil evidence), all different from one another. Results: The results show that the proposed indexes well describe and characterize each locality. Most of the sites are moderately vulnerable (V between 1 and 3) except for large quarry sites (e.g., Pirro Nord, Italy and Solnhofen, Germany) whose vulnerability indexes fell in the maximum degree of risk. Discussion: The operational procedure presented here is a simple, objective, and remotely applicable method allowing paleontologists and non-expert personnel to categorize localities and, therefore, act as a base to plan actions in paleontological heritage management relative to territorial development and land use.